Harmiyyat al-ḥājiyyah li-l-insān fī fīlm al-Khalāṭ+ li-Fahd al-Māriy (Dirāsah ʿilm al-nafs al-adabī) - Yena Kurniasih, Annisa (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Alkhallat+ is an anthology film that portrays stories reflecting the culture and daily lives of people in Saudi Arabia. The film presents four different narratives centered on themes of deception and manipulation in various social situations. Each story conveys a distinct message, namely theft, morality, infidelity, and dishonesty. However, all four narratives share a common thread: every human action generates social factors that dominate the impact of those actions. The characters in each story display diverse personality traits, highlighting various aspects of human behavior and the consequences that arise from individual actions. The purpose of this study is to examine the humanistic values embodied by the characters in the film Alkhallat+. This research employs a literary psychology approach based on Abraham Maslow’s humanistic theory of the hierarchy of needs. Using a qualitative approach and content analysis method, the primary data source of this study is the film Alkhallat+. The findings indicate that characters such as Turky, Sara, and others exhibit diverse psychological responses to life pressures, love, the pursuit of self-esteem, and efforts toward self-actualization. Physiological needs, safety needs, love and belonging, esteem, and self-actualization are depicted realistically throughout the narrative.